Exosomes derived from miR-26a-5p-modified adipose mesenchymal stem cells improve wound healing by targeting MAP2K4 - Chen, Kana; Ye, Wei; Chi, Longjun; Xie, Shujie (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAbnormal wound healing impairs bodily functions and burdens healthcare systems. Adipose mesenchymal stem cells (AMSCs)-derived exosomes promote wound healing, with exosomal microRNAs (miRNAs) playing pivotal roles. This study investigated the roles and mechanisms of miR-26a-5p (delivered by AMSCs-derived exosomes) in wound healing.MethodsThe GSE55661 dataset was analyzed to screen a crucial miRNA (miR-26a-5p) and its target gene (MAP2K4), and their interaction was further validated by dual-luciferase reporter gene assay. Exosomes were isolated from miR-26a-5p-overexpressing AMSCs, and a mouse skin defect model was used to evaluate their effects on wound healing.ResultsBioinformatics identified 13 differentially expressed miRNAs, and a miRNA-mRNA regulatory network composed of 12 DEmiRNAs and 143 regulated target genes was built. In this network, miR-26a served as the hub node, and the target genes were enriched in the MAPK cascade, as well as cAMP, relaxin, Hippo, Apelin, Wnt, and cGMP-PKG signaling pathways. Thereafter, MAP2K4 was identified as the target of miR-26a-5p, and exosomes were successfully isolated from AMSCs overexpressing miR-26a-5p. Exosomes from miR-26a-5p overexpressed AMSCs (like miR-26a-5p agomir) could facilitate wound healing, and down-regulated MAP2K4, Il6, Il1β, and Tnf-α, whereas up-regulated Col1a1, Cd31, Col2a1, α-Sma, and Col3a1.DiscussionAMSCs-derived exosomes delivering miR-26a-5p may expedite wound healing by targeting MAP2K4, inhibiting inflammation, and enhancing angiogenesis and ECM synthesis.